2022
DOI: 10.3389/fpsyg.2022.832520
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Relationships in Community and Clinical Samples: Their Importance for Mental Health

Abstract: Meaningful relationships are centrally important for human functioning. It remains unclear, however, which aspects of meaningful relationships impact wellbeing the most and whether these differ between psychiatric patients and members of the community. Information about relationship attributes and functions were collected in community members (N = 297) and psychiatric patients (N = 177). Relationship attributes and functions were examined for differences between groups (community vs. patients), their impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
2
0
2
Order By: Relevance
“…A potential explanation for these findings may be the fact that the history taking covering private matters, e.g., sexual relationships, history of psychiatric illness, etc., or the physical examination of private body parts requires a deeper relationship and/or a higher degree of trust than the history taking concerning less private matters or the physical examination of body parts not considered private. Moreover, another factor in this regard is the fact that it is more common for individuals with psychiatric illnesses may have a deficit in fulfilling relationships with others or have problems with mistrust of others than it is for other patients [ 11 ]. Additionally, this study found that having prior experience of medical examination by an LGBTQ + physician did not lead to different attitudes toward LGBTQ + physicians than having no such experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential explanation for these findings may be the fact that the history taking covering private matters, e.g., sexual relationships, history of psychiatric illness, etc., or the physical examination of private body parts requires a deeper relationship and/or a higher degree of trust than the history taking concerning less private matters or the physical examination of body parts not considered private. Moreover, another factor in this regard is the fact that it is more common for individuals with psychiatric illnesses may have a deficit in fulfilling relationships with others or have problems with mistrust of others than it is for other patients [ 11 ]. Additionally, this study found that having prior experience of medical examination by an LGBTQ + physician did not lead to different attitudes toward LGBTQ + physicians than having no such experience.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the attitudes toward LGBTQ + physicians and their associating factors among individuals with psychiatric illnesses, who are a vulnerable population, have not, to our knowledge, been studied before in the Thai context. Because individuals with psychiatric illnesses may have a deficit in fulfilling relationships with others or have problems with mistrust of others [ 11 ]. Limited data exist concerning these issues in Thailand in general and in the Southern Region in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Hubungan keluarga yang baik memengaruhi kualitas hidup sebagian besar orang, dan cara keluarga berfungsi juga memengaruhi fungsi masyarakat secara keseluruhan [1]. Hubungan keluarga yang berkualitas tinggi telah terbukti menjadi faktor pelindung bagi kesehatan mental dan mencegah timbulnya pengalaman yang merugikan seperti stres dan depresi [2]. Selain itu, hubungan keluarga yang lebih baik dikaitkan dengan berkurangnya tekanan psikologis, peningkatan kepuasan hidup, dan ketahanan yang lebih kuat [3].…”
Section: Pendahuluanunclassified
“…Pada penelitian pada anak-anak dan remaja, ditemukan bahwa komunikasi keluarga yang buruk dapat menyebabkan risiko masalah perilaku yang semakin tinggi [24], [25]. Bidang keilmuan psikologi perkembangan banyak mendokumentasikan pentingnya kualitas hubungan termasuk komunikasi keluarga terhadap perkembangan anak-anak atau remaja dalam keluarga, meskipun begitu, wawasan terkait hubungan antara kualitas hubungan dan kesejahteraan pada konteks yang lebih luas seperti pada orang dewasa masih sulit diketahui [2], [26], [27]. Pada ibu dan anak perempuan sendiri, ditemukan bahwa komunikasi antara ibu dan anak yang positif akan memengaruhi resiliensi anak perempuan ketika dewasa.…”
Section: Pembahasanunclassified